I'm trying to refresh myself on the subject.

If φ= (L1 ∨...∨ Ln) whereL1,...,Ln are literals, then{L1, ..., Ln}is the clause associated to φ.

How would I convert ¬(¬P ∨ Q) to a clause?


To convert to clauses, you first need to put your expression into CNF:

$\neg (\neg P \lor Q) \Leftrightarrow \neg \neg P \land \neg Q \Leftrightarrow P \land \neg Q$

Now that it is in CNF, you know that each conjunct is a generalized disjunction that can be made into a clause. In this case, you have two conjuncts, so you will get two clauses: $\{ P \}$ and $\{ \neg Q \}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.